miR-504 Promoted Gastric Cancer Cell Proliferation and Inhibited Cell Apoptosis by Targeting RBM4 - Yi Zhang; Hongmei Yong; Jing Fu; Guangyi Gao; Huichang Shi; Xueyi Zhou; Mingsheng Fu (Journal of Immunology Research)
Background. The purpose of this study was to explore the role and underlying mechanism of miR-504 and RBM4 in gastric cancer. Methods. The qRT-PCR or Western blot was performed to determine the expressions of miR-504 and RBM4 in the gastric cancer tissues and normal tissues. Human SGC-7901 cells were transfected with miR-504 mimic/inhibitor or pcDNA-RBM4. Cell proliferation and cell apoptosis were assessed by colony formation assay and flow cytometry, respectively. Luciferase reporter gene assays were used to investigate interactions between miR-504 and RBM4 in SGC-7901 cells. Results. The relative expression of miR-504 was significantly upregulated in the gastric cancer group (n=25) than in the paired normal group (n=25), but the relative RBM4 expression was remarkably downregulated in the gastric tumor group, compared with the normal group. Additionally, miR-504 overexpression increased the viability of gastric cancer cells. Moreover, RBM4 is a functional target of miR-504 in gastric cancer cells. miR-504 was further confirmed to promote SGC-7901 cell proliferation and inhibit cell apoptosis by downregulation RBM4 in vitro. Conclusions. miR-504 promotes gastric cancer cell proliferation and inhibits cell apoptosis by targeting RBM4, and this provides a potential diagnostic biomarker and treatment for patients with gastric cancer.